CO2 sensing by connexin26 and its role in the control of breathing. Issue 2 (12th February 2021) - Dale, Nicholas
Abstract : Breathing is essential to provide the O2 required for metabolism and to remove its inevitable CO2 by-product. The rate and depth of breathing is controlled to regulate the excretion of CO2 to maintain the pH of arterial blood at physiological values. A widespread consensus is that chemosensory cells in the carotid body and brainstem measure blood and tissue pH and adjust the rate of breathing to ensure its homeostatic regulation. In this review, I shall consider the evidence that underlies this consensus and highlight historical data indicating that direct sensing of CO2 also plays a significant role in the regulation of breathing. I shall then review work from my laboratory that provides a molecular mechanism for the direct detection of CO2 via the gap junction protein connexin26 (Cx26) and demonstrates the contribution of this mechanism to the chemosensory regulation of breathing. As there are many pathological mutations of Cx26 in humans, I shall discuss which of these alter the CO2 sensitivity of Cx26 and the extent to which these mutations could affect human breathing. I finish by discussing the evolution of the CO2 sensitivity of Cx26 and its link to the evolution of amniotes.